LESBIAN, GAY, BISEKSUAL, TRANSGENDER (LGBT) PERSFEKTIF IMAM SYAFI’I, HUKUM ISLAM DAN HUKUM POSITIF - H Suwardin (Universitas Islam Negeri Fatmawati Sukarno, 2018)
This research raises about Had for Lesbians, Gay, Bisexual, Transgender (LGBT) Perspective of Imam Shafi’i, Islamic Law and Positive Law. This research method is library research. The results of this study indicate that Had Lesbi- an, Gay, Bisexual, Transgender (LGBT) according to Imam Syafii Imam Syafii’s opinion about LGBT is considered a very damned act and is considered as jarimah regardless of the perpetrators, whether done by unmarried people or people those who are married, it is referred to as fahisyah and is regarded as against the law. It also does not reduce its criminal value, even though it is done voluntarily or like it. Although no one feels aggrieved, it is still seen as a very despicable sexual violation, without knowing priorities. Had in the Islamic law perspective on Lesbians, Gay, Bisexual, Transgender (LGBT) that LGBT punished this behavior seen from the side where he channeled his lust for the same sex. So, if he were a man, when he channeled lust desires to fellow men, then the law was included in the category of gay (liwath) and if he was a woman, when channeling his lust for others, then the law was included in the category of lesbian . the scholars also agreed that the clerics forbid transgender behavior